Perniagaan Online Syariah: Suatu Kajian dalam Perspektif Hukum Perikatan Islam - Suhartono, Suhartono - (IAIN Salatiga, 2010)
Along the vast development in information technology, it creates a newÂ variant in business relation, that once was primarily physical with papers asÂ the transaction mechanism tools, shifts into a more virtual relationshipÂ pattern using digital media or well known as electronic commerce (ecommerce).Â There has been a transformation in the jurisdictional review towardsÂ agreement forms, from the conventional trading using textual documentÂ with â€œtinta basahâ€ and physical contact in a real space, into a digital modelÂ where all the documents are made in a cyber space.This transaction model provides several benefits within its operational,Â nevertheless its presence also emerges new complex legal problems regardingÂ the legality of a contract or an agreement, especially in the Islamic lawÂ perspective. Does an Islamic bonding law also accommodate this ecommerce transaction model?